2010
DOI: 10.1002/cyto.a.20853
|View full text |Cite
|
Sign up to set email alerts
|

Detection and classification of thyroid follicular lesions based on nuclear structure from histopathology images

Abstract: Follicular lesions of the thyroid are traditionally difficult and tedious challenges in diagnostic surgical pathology in part due to lack of obvious discriminatory cytological and microarchitectural features. We describe a computerized method to detect and classify follicular adenoma of the thyroid, follicular carcinoma of the thyroid, and normal thyroid based on the nuclear chromatin distribution from digital images of tissue obtained by routine histological methods. Our method is based on determining whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 49 publications
4
117
0
3
Order By: Relevance
“…Many other methods collect features from either the original RGB image, a converted image to other non-biologically based color spaces (e.g., Lab or HSL), or from a grayscale version of that same image (Al-Kadi, 2010;Basavanhally et al, 2010;Dundar et al, 2011Dundar et al, , 2010Esgiar et al, 2002;Farjam et al, 2007;Glotsos et al, 2008;Huang and Lee, 2009;Jafari-Khouzani and SoltanianZadeh, 2003;Kong et al, 2009;Ozolek et al, 2014;Petushi et al, 2006;Qureshi et al, 2008;Ruiz et al, 2007;Schnorrenberg et al, 1997;Tabesh et al, 2005;Tabesh and Teverovskiy, 2006;Tahir and Bouridane, 2006;Thiran and Macq, 1996;Tuzel et al, 2007;Wang et al, 2010;Wetzel et al, 1999;Weyn et al, 1998;Xu et al 2014aXu et al , 2014b. Since hematoxylin binds to nucleic acids and eosin binds to protein, unmixing the stains allows the feature extraction to directly probe the state of these important biological molecules, whereas features from the mixed image may either miss this signal or be unable to probe them independently.…”
Section: Discussionmentioning
confidence: 99%
“…Many other methods collect features from either the original RGB image, a converted image to other non-biologically based color spaces (e.g., Lab or HSL), or from a grayscale version of that same image (Al-Kadi, 2010;Basavanhally et al, 2010;Dundar et al, 2011Dundar et al, , 2010Esgiar et al, 2002;Farjam et al, 2007;Glotsos et al, 2008;Huang and Lee, 2009;Jafari-Khouzani and SoltanianZadeh, 2003;Kong et al, 2009;Ozolek et al, 2014;Petushi et al, 2006;Qureshi et al, 2008;Ruiz et al, 2007;Schnorrenberg et al, 1997;Tabesh et al, 2005;Tabesh and Teverovskiy, 2006;Tahir and Bouridane, 2006;Thiran and Macq, 1996;Tuzel et al, 2007;Wang et al, 2010;Wetzel et al, 1999;Weyn et al, 1998;Xu et al 2014aXu et al , 2014b. Since hematoxylin binds to nucleic acids and eosin binds to protein, unmixing the stains allows the feature extraction to directly probe the state of these important biological molecules, whereas features from the mixed image may either miss this signal or be unable to probe them independently.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear datasets were segmented as described in ref. 10. The liver dataset were segmented to have 500 nuclei with an average of 50 nuclei per patient.…”
Section: Methodsmentioning
confidence: 99%
“…The first application is concerned with discovering the principal differences in nuclear chromatin arrangement between normal, benign, and malignant cells extracted from the liver and thyroid of pediatric patients (10). Nuclear structure has long been a highly used biomarker in image-based pathology.…”
Section: Significancementioning
confidence: 99%
“…Another direction aims at performing a better segmentation of the image before further processing with the hope that the segmented objects (cell or nucleus) could represent the characteristics of the whole images better. Wang et al indicated that the classification accuracies could reach 100% using a simple nearest neighbor classification algorithm on testing instances after segmenting the nuclei region from the original image and extracting features of chromatin patterns based on the segmented image [18]. A similar work in [19] also showed that extracting features from the gland and nuclei areas which were segmented from the original images gave promising results in prostate cancer grading, breast cancer detection, and breast cancer grading.…”
Section: Introdutionmentioning
confidence: 99%